The Implementation to Pasung Among People with Mental Illness in Terms of Health Policy in Indonesia - Syalisa Syabil; Ummi Rahma; Zahra Septina; Adjrina Dawina Putri; Riswandy Wasir (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
More than 90% of people with mental illness in Indonesia do not get any treatment and tens of thousands of people with psychosis are illegally detained in pasung by their families at home. Much of the use of pasung with people with a history of mental illness is believed to be due to their failure to continue their medication. This study aims to discuss the law that related to the use of pasung, the perception of pasung, the impact of pasung, as well as the strategies to overcome the use of pasung in Indonesia. The method used in this study is a literature review. PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-analyses) model is used for complete and detailed steps for conducting a literature review. Literature searched by search engine machine Google Scholar as well as journal databases, such as Connected Papers and Elsevier. Based on the six articles, pasung is chosen by the family to avoid harmful actions and follow the stigma in society which actually will delay the patient's recovery. In order to overcome the use of pasung in people with mental disorders, family and the surrounding play a major role in this practice. Besides, awareness of mental health can be the first step in reducing the incidence of using pasung and the role of the government in providing adequate health services.